Cellular model system to dissect the isoform-selectivity of Akt inhibitors - Lena Quambusch (Nature Portfolio, 2021)
Elucidating specific effects of protein kinase Akt isoforms remains challenging. Here, the authors establish an Akt isoform-dependent cellular model system and use it, together with X-ray crystallography and structure-based ligand design, to develop isoform-selective covalent-allosteric Akt inhibitors